Physical activities, resources and challenges in implementation of physical education programme among public primary schools in Kampala Uganda - Ismail Asiimwe; J.F Babalola; Shallon Atuhaire (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Physical activities among young people provide an opportunity to develop the values, and skills for an active lifestyle and high self-esteem. Physical Education as one of the subjects in schools covers this essential role, although its’ provision mostly in the developing world has declined in many countries. This study assessed the physical activities, resources, and challenges in the implementation of Physical Education program among public primary schools in Kampala, Uganda. It was a descriptive survey design employing a semi-structured questionnaire to collect data among teachers and headteachers. Data were analyzed using frequencies, and Pearson product-moment correlation was determined at 0.05 level of significance. Findings reveal availability of facilities (r=0.374), trained personnel (r=0.654), equipment (r=0.529) and school enrolment (r=0.622) having a significant relationship with implementation of PE program. Traditional games, athletics, and ball games were the main activities. Insufficient resources and less value attached to these activities remain the major challenges. Resource allocation and sensitization on the value of physical education could enhance the implementation of the physical education program in public schools.